2016
DOI: 10.3233/jad-160479
|View full text |Cite
|
Sign up to set email alerts
|

Relative Alterations in Blood-Based Levels of Sestrin in Alzheimer’s Disease and Mild Cognitive Impairment Patients

Abstract: Sestrins (sesn) are highly conserved proteins that play an important neuroprotective role, in part as a consequence of their antioxidative capacity, which prevents reactive oxygen species formation. In this study, we evaluated the concentrations of sesn1 and sesn2 in the serum of 41 Alzheimer's disease (AD) patients, 27 mild cognitive impairment (MCI), and 60 elderly controls, by surface plasmon resonance, which was validated by using western blot. Moreover, the mRNA level of sestrins in all the study groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
1
22
1
Order By: Relevance
“…Peripheral blood biomarkers for early diagnosis have been examined in many diseases including AD [40][41][42]. In addition, various blood biomarkers associated with neurocognitive impairments have been reported, for example, glucose [43][44][45] and atherogenic index of plasma (AIP) [46].…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood biomarkers for early diagnosis have been examined in many diseases including AD [40][41][42]. In addition, various blood biomarkers associated with neurocognitive impairments have been reported, for example, glucose [43][44][45] and atherogenic index of plasma (AIP) [46].…”
Section: Discussionmentioning
confidence: 99%
“…Sesn2 is a critical factor mediating reactive oxygen species formation, in part by inhibiting AMPK pathway member mTORC1 (Ebnoether, Ramseier, Cortada, Bodmer, & Levano-Huaman, 2017). Sesn2 is also induced by Ab exposure in vitro and upregulated in serum of AD patients (Chen, Chen, Wu, Huang, & Yang, 2014;Rai et al, 2016). Therefore, normalization of the AMPK cascade and/or downstream signaling pathway members, as seen with MCS, may be considered therapeutic targets in DS and AD.…”
Section: Cellular Homeostasis Regulationmentioning
confidence: 99%
“…Chen et al demonstrated that Sesn2 is induced by amyloid β-peptide, which is a biomarker of Alzheimer’s disease, and protects cortical neurons against amyloid β-peptide by regulating autophagy [58]. In addition, clinical study showed that the serum levels of Sesn2 were significantly increased in the Alzheimer’s disease group compared to mild cognitive impairment, and elderly controls [59]. Another study indicated that Sesn2 is upregulated in the midbrains from Parkinson’s disease patients [60].…”
Section: Sesns In the Nervous Systemmentioning
confidence: 99%